Quantificação do EGF na saliva e em lesões de pacientes com leucoplasias bucais: estudo caso-controle - Filipe Jaeger de Oliveira (2014)
Oral leukoplakia (OL) is the main potentially malignant disorder, defined as a white patch or plaque of questionable risk that can not be diagnosed clinically or pathologically as any other disease. Several factors such as the location of the lesions, smoking habits, and histologic atypia have been associated with the malignant transformation of these lesions. The epidermal growth factor (EGF) is a polypeptide of 53 amino acids, originally isolated from the salivary glands of mice. Some evidences indicates that EGF is a protective factor against tissue injuries. Previous studies have demonstrated that salivary EGF levels are reduced in patients with oral squamous cell carcinoma (OSCC). Therefore, the aim of this study was to assess the salivary levels of EGF in patients with OL and compare with clinically healthy individuals. Additionally, the tissue expression of EGF and its receptor (EGFR) were evaluated by immunohistochemistry and clinicopathologic aspects were compared with those of EGF and salivary levels in tissue immunostaining. Data were analyzed in SPSS 21.0 and GraphPad Prism 5 (significance level p < 0.05 ). Salivary EGF levels were measured in the saliva of 32 case and control patients, using ELISA. It was found that EGF salivary levels were lower in patients with OL compared to the control group, although the difference was not statistically significant. There was no association between salivary levels and immunohistochemical expression of EGF. Strong immunoreactivity of EGF was associated with multiple lesions. It was observed a tendency of lesions located in high risk shows positive imunoexpression of EGF. This study concludes that there is no difference of salivary EGF levels between patients and controls. Further studies are needed to elucidate the role of EGF in the progression of oral cancer.